The role of advertising in promoting society’s awareness of children’s rights and enhancing effective listening to the voices of children: An analytical study of the effects and challenges - DR: BASANT AYADA; Dr. SAMEER BANI YASSEN; MASHAEL AL SHAMSI; ASMAA MOHAMED; HIND AL HAMMADI (International Journal of Multidisciplinary Research and Studies, 2023)
The study aimed to gain a deeper understanding of the importance of protecting children's rights and ensuring their healthy and sustainable development. Children are the fundamental building blocks of any society, and a better understanding of their needs, feelings, and opinions can contribute to creating a better environment for them and helping them build their personalities. Additionally, the study promotes healthy family and social relationships by focusing on effective listening to children within the family, which can reduce tensions and enhance understanding among family members. Furthermore, the study sheds light on the challenges and issues related to children's rights and highlights them to guide efforts toward effective solutions. Ultimately, the study contributes to achieving better child development and broader societal goals by increasing awareness of the importance of children's rights and developing policies and practices based on the principle of respecting those rights.